2011
DOI: 10.1103/physrevb.84.092105
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular oxygen tetramer (O2)4: Intermolecular interactions and implications for theεsolid phase

Abstract: Recent data have determined that the structure of the high-pressure phase of solid oxygen consists of clusters composed of four O 2 molecules. This finding has opened the question about the nature of the intermolecular interactions within the molecular oxygen tetramer. We use multiconfigurational ab initio calculations to obtain an adequate characterization of the ground singlet state of (O 2 ) 4 , which is compatible with the nonmagnetic character of the phase. In contrast to previous suggestions implying cov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The approach should allow, even if at the approximate mean field level, for the presence of molecular spin whenever that should lower the total enthalpy. (ii) Describe the nature, stability, and optical properties of the resulting model S = 1 collective singlet state description of e 1 -O 2 , extending that in literature (12,13), particularly including quantum fluctuations. (iii) Predict the new phase diagram displaying a first-order e 1 -e 0 low temperature phase transition near 20 GPa, and a novel phase line predicting at high temperature a new critical point roughly at 30 GPa and 200 K inside the broad e-O 2 phase.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…The approach should allow, even if at the approximate mean field level, for the presence of molecular spin whenever that should lower the total enthalpy. (ii) Describe the nature, stability, and optical properties of the resulting model S = 1 collective singlet state description of e 1 -O 2 , extending that in literature (12,13), particularly including quantum fluctuations. (iii) Predict the new phase diagram displaying a first-order e 1 -e 0 low temperature phase transition near 20 GPa, and a novel phase line predicting at high temperature a new critical point roughly at 30 GPa and 200 K inside the broad e-O 2 phase.…”
mentioning
confidence: 70%
“…Our work has the following aims: (i) Provide first principles quantitative calculations of electronic and vibrational properties of same quality for both ǫ 0 -O 2 and ǫ 1 -O 2 , including Raman and IR vibrational frequencies and intensities that could be compared with experiment in both regimes. The approach should allow, even if at the approximate mean field level, for the presence of molecular spin whenever that should lower the total enthalpy; (ii) Describe the nature, stability, and optical properties of the resulting model S=1 collective singlet state description of ǫ 1 -O 2 , extending that in literature 12,13 , particularly including quantum fluctuations and ; (iii) Predict the new phase diagram displaying a first order ǫ 1 − ǫ 0 low temperature phase transition near 20 GPa, and a novel phase line predicting at high temperature a new critical point roughly at 30 GPa and 200 K inside the broad ǫ-O 2 phase.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although it has been shown that DFT methods are less accurate than for weakly bound systems (Bartolomei et al, 2011 , 2014 ), in this particular case, and concerning the relative energies between the gG'T and gG'G conformers, we can state that the B3LYP calculation (Δ E e = 1.22 kJ mol −1 ; Δ E 0 = 1.32 kJ mol −1 ) better reproduces the experimentally determined value of 1.9 (3) kJ mol −1 (Penn and Curl, 1971 ) with respect to the MP2 one (Δ E e = 0.46 kJ mol −1 ; Δ E 0 = 0.65 kJ mol −1 ). The same is true also for the methyl internal rotation barrier: the experimental value for the gG'T and g'GG conformers are 11.9 and 9.7 kJ mol −1 respectively, while the two values [B3LYP and MP2/6-311++G(d,p)] are 11.8/12.7 and 9.8/10.7 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%